Distribution of Women’s Ideology in Indonesian Islamic Novels: A Study Based on Erik Olin Wright’s Class Theory - Taswirul Afkar; Wawan Hermawan; Wiwik Mardiana (DISASTRA: PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2026)
This study aims to analyze the distribution of women’s ideologies in Indonesian Islamic novels through four dimensions of Erik Olin Wright’s class theory—class structure, class formation, class consciousness, and class struggle—strengthened by the perspectives of agency, intersectionality, and Bourdieu’s concept of cultural capital. The method employed is a qualitative approach with a content analysis design. The research data consist of narrative excerpts, dialogues, and events that represent class positions, forms of capital, and negotiation strategies of female characters. The data sources are four commercially published novels: Hati Suhita, Perempuan Berkalung Sorban, Assalamualaikum Beijing, and Dalam Mihrab Cinta. The findings show that stratification is primarily shaped by religious-cultural capital and symbolic capital, placing women in contradictory class locations: they gain recognition of social status but are constrained in authority and decision-making. Class formation shifts through experiences of life in Islamic boarding schools, marriage, education, and diasporic contexts. Class consciousness develops from acceptance toward a critical reading of gendered religious authority, while class struggle appears in the form of negotiation, identity affirmation, education/writing, and cross-positional solidarity. In conclusion, Wright’s framework is effective for comparatively mapping the dynamics of women’s class positions and is relevant as a pedagogical tool in literature learning to foster critical literacy and gender awareness.